Neonatal heart rate variability in type 1 diabetic pregnancy. (16th November 2010) - Russell, NE; Higgins, MF; Kinsley, B; Foley, M; McAuliffe, FM
Abstract : Introduction: In adult diabetic patients, abnormalities in heart rate variability can predict mortality post myocardial infarction. Fetuses of diabetic mothers are at increased risk of unexplained death in utero and it is possible that there may be an association with underlying alterations in fetal autonomic function. The objective of this study is to determine if neonatal autonomic function differs between normal and pregestational type 1 diabetic pregnancy. Methods: Thirty-eight patients with pregestational type 1 diabetes mellitus and 26 healthy controls were prospectively recruited. All patients had neonatal heart rate variability assessed using Powerlab (AdiInstruments) and cord blood sampling for arterial and venous pH and glucose was performed. Results: Significant differences were found between the two cohorts. In the diabetic cohort, there was increased overall power, increased low frequency (LF), decreased high frequency (HF) with an increased LF:HF ratio, (p values 0.016, 0.016 and 0.042, respectively) reflecting sympathetic over activity. These differences were independent of gestational age and birthweight centile. There were also significant associations between heart rate variability and fetal academia (p=0.01) and maternal and fetal glycaemic control (p<0.05 and p=0.019, respectively). Conclusion: This study shows significant evidence of autonomic dysfunction in neonates of type 1 diabetic mothers. This may be related to the effect of prolonged fetal exposure to the hyperglycaemic milieu of diabetic pregnancy. Autonomic dysfunction may have a role in unexplained fetal death as it is influenced by acidosis and hyperglycaemia; features associated with fetal death in pregestational diabetic pregnancy.